A quinta história: composições da educação matemática como área de pesquisa - Fernandes, Filipe Santos [UNESP] (2014)
This research aimed to elaborate comprehensions about how Mathematics Education has been constituted itself as a research area. For that, we used memorials written for exams of Habilitation (Professorship) by Arlete de Jesus Brito, Marcelo de Carvalho Borba and Wagner Rodrigues Valente. All of those researchers were interviewed, what helped us problematize the existing ways of Mathematics Education that these narratives could generate and run in their own aspects of scientificity and historicity. Then five stories of Mathematics Education were delineated, all of them in the perspective of a fictional esthetics, all of them done in a singular and local way situated in the micropolitics established in the research, in a movement which gives centrality to the narrative experience. In those stories we treated themes such as the boundaries between the inside and the outside of Mathematics Education (First Story); the constitution of Mathematics Education by means of strategies of power (Second Story); the different ways in which Mathematics Education can operate (Third Story); the (in)subordination of Mathematics Education to other disciplines (Fourth Story); and the multiple possibilities that those life narratives can open (Fifth Story). Besides that, we address in the other chapters themes such as the relation between narrative, experience and history; the narrative investigation within Mathematics Education; aspects of scientificity within Mathematics Education; the mobilization of memorials as resources for research in History of Mathematics Education; and the potentiality of fiction for this work composition